THE BEGINNINGS OF BUSINESS BUDGETING. - Theiss, Edwin L. (The Accounting Review, 1937)
Abstract The object of all business enterprises from earliest times has been the making of profit and the acquisition of more wealth. Budgeting occupies a prominent and permanent place in the field of business administration. Although budgeting, in the modern sense, was a postwar development in business management and had extensive application first in the United States, the beginnings of budgetary procedure of various other countries is also discussed in the article. Some of the European countries have recently been adopting budgetary procedures in their industries. Germany seems to be taking the lead. French business journals have contained reports of successful budgetary developments in the United States and some accounts of experiments carried on in French industries. In Russia the famous five year plan for economic production has centralized business budgeting in the machinery of the national Soviet government, while in Italy the national government also directs and controls to a large degree industrial operations. Belgium and Switzerland are also making some progress in the application of budgetary procedures.